2017
DOI: 10.15740/has/au/12.3/399-404
|View full text |Cite
|
Sign up to set email alerts
|

Utilization pattern of mobile phone technology (Smartphone) among the farmers of Nagaur district in Rajasthan

Abstract: Now-a-days, one of the most important emerging tools of ICT is the mobile phones with a remarkable growth during last decade. Mobile phone technologies have provided a good platform for farmers to share their knowledge and information among each other in time such as weather information, crop and variety selection, fertilizer and irrigation management, disease and pest management, market prices of the product and ongoing government programmes. Keeping this in view, a study was conducted assess the utilization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 5 publications
3
3
0
Order By: Relevance
“…As far as ICT utilization is concerned, the results are in support of the reports of Ndag et al, (2008) who reported that the ICT utilization among majority of respondents from North-central Nigeria was moderate to high. It is also in agreement with the results of Kailash et al, (2017) in which the ICT utilization level of farmers was found to be high. This paves the path towards better adoption of new technologies as suggested by Monikha et al, (2021) that Expert system helped farmers to take decisions to adopt different management practices.…”
Section: Resultssupporting
confidence: 92%
“…As far as ICT utilization is concerned, the results are in support of the reports of Ndag et al, (2008) who reported that the ICT utilization among majority of respondents from North-central Nigeria was moderate to high. It is also in agreement with the results of Kailash et al, (2017) in which the ICT utilization level of farmers was found to be high. This paves the path towards better adoption of new technologies as suggested by Monikha et al, (2021) that Expert system helped farmers to take decisions to adopt different management practices.…”
Section: Resultssupporting
confidence: 92%
“…Most of the farmers under this study has adopted the same pattern. Present observations are well supported by previous studies similar in this regards [8,4]. They have also observed that, most of the respondents follow dairy farming as a subsidiary occupation.…”
Section: Resultssupporting
confidence: 92%
“…Comparable findings were also noted by Mutunga et al [11] wherein, most of the (38.4%) respondents used their phones to send and receive both text and voice messages. Parallel findings were also revealed in the study of Kailash et al [4]. Their findings were from Rajasthan and it was observed that, most of the respondents were internet users (29.09%) followed by what's app (27.27%), facebook (19.09%), newsletter (18.18%), farm publication and online video (13.63%), e-mail (10%) and twitter (4.54%).…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…This may lead to lose the credibility on information service providers like universities, SDAs etc. Mobile phone is becoming an all-time partner to all the individuals and farmers were also now-a-days having mobile phones [1,2]. Sending information to the mobile is easy and scalable.…”
Section: Introductionmentioning
confidence: 99%